Synopsis of the genus Tragus (Poaceae: chloridoideae: cynodonteae) in Peru - Muñuico, Jhon W.; Quipuscoa-Silvestre, Victor; Gutiérrez, Harol (Phytotaxa, 2025)
A taxonomic synopsis of the genus Tragus for Peru is presented. Tragus peruvianus is described as a new species, while T. australianus and T. racemosus are excluded from the Peruvian agrostological flora. A taxonomic key, morphological descriptions, ecological information, notes, iconography, and reference images are provided.